Antifungal activities of surfactant protein D in an environment closely mimicking the lung lining. (January 2019) - Ordonez, Soledad R.; van Eijk, Martin; Escobar Salazar, Natalia; de Cock, Hans; Veldhuizen, Edwin J.A.; Haagsman, Henk P.
Highlights: A model system mimicking the lung lining was developed. Surfactant protein D (SP-D) protects against C. albicans and A. fumigatus. SP-D binds to these fungi and prevents fungal adhesion to the epithelium. SP-D binding induces neutrophil accumulation and fungal clearance at the lining. Abstract: At the lung lining innate defenses protect our lungs against inhaled fungal cells that could pose a threat to our health. These defenses are comprised of mucociliary clearance, soluble effector molecules and roaming phagocytic cells, such as macrophages and neutrophils. How important each of these defenses is during fungal clearance depends on the specific fungal pathogen in question and on the stage of infection. In this study the localization and antifungal activity of the lung surfactant protein D (SP-D) was studied in an environment mimicking the lung lining. To this end Calu-3 cells were grown on an air-liquid interface allowing them to polarize and to produce mucus at their apical surface. Additionally, neutrophils were added to study their role in fungal clearance. Two fungal pathogens were used for these experiments: Candida albicans and Aspergillus fumigatus, both of clinical relevance. During fungal infection SP-D localized strongly to both fungal surfaces and stayed bound through the different stages of infection. Furthermore, SP-D decreased fungal adhesion to the epithelium and increased fungal clearance by neutrophils from the epithelial surface. These findings suggest that SP-D plays an important role at the different stages of pulmonary defense against fungal intruders.